Thermal properties of cryo-ground fenugreek powder - S N Saxena, P Barnwal, K K Singh, R Kumar, (Journal of Spices and Aromatic Crops, 2015)
Thermal properties, viz., specific heat, thermal conductivity and thermal diffusivity of fenugreek (cv. AM-2) powder were determined. Specific heat increased from 295.9 to 5794.4 J kg-1 K-1 with increasing temperature from -150°C to 100°C and moisture content from 5.5% to 25.2% d.b. and exhibited second order polynomial relationship. Thermal conductivity and thermal diffusivity ranged from 0.140-0.186 W m-1 K-1 and 8.13 × 10-6-11.38 × 10-6 m2 s-1, respectively with increasing moisture content. Thermal conductivity and thermal diffusivity showed quadratic relationships with moisture content. Specific heat of fenugreek powder was significantly affected by moisture content and temperature (P<0.01), while thermal conductivity and thermal diffusivity were significantly affected by moisture content (P<0.01).